Excel cookbook - Griffiths, Dawn (O'Reilly Media, Inc., 2024)
Filled with tips, tricks, and techniques, this easy-to-use book is the perfect resource for intermediate to advanced users of Excel. You'll find complete recipes for more than a dozen topics covering formulas, PivotTables, charts, Power Query, and more. Each recipe poses a particular problem and outlines a solution that you can put to use right away--without having to comb through tutorial pages. Whether you're a data analyst, project manager, or financial analyst, author Dawn Griffiths directs you straight to the answers you need. Ideal as a quick reference, Excel Cookbook is also perfect for learning how to work in a more efficient way, leading to greater productivity on the job. With this book, you'll jump in and get answers to your questions--fast.
Keywords: Microsoft Excel (Computer file)